Investigation on subcooled flow boiling heat transfer characteristics in ICE-like conditions - Hu Xiaoyu (De Gruyter, 2021)
The increasing demand of cooling in internal combustion engine (ICE) may require the shift of heat removal method from traditional single phase liquid convection to subcooled flow boiling in order to fulfill the desired functional temperature. Thus, the characteristics of subcooled flow boiling heat transfer should be studied exclusively considering the practical conditions in ICEs. Accordingly, in this article, subcooled flow boiling experiments were conducted in a rectangular channel using 50/50 volume mixture of ethylene glycol and water coolant (EG/W) as working fluid. Aluminum and cast iron surfaces were selected as the heated surfaces to simulate the material of cylinder head in gasoline and diesel engines, respectively. Experimental results showed a trend that the aluminum surface had a better performance than the cast iron surface in terms of heat transfer coefficient in the boiling region. The difference between these two surfaces was concluded as results of different surface thermophysical properties. A modified wall heat flux model was proposed based on the power-type addition method. The proposed model modified the nucleation boiling contribution by introducing a new parameter which accounts for the influence of thermophysical properties of heated surface on the boiling process. Thus, one such modified model could be useful for practical engine cooling applications.